If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 52 = 41 + -1u Solving 52 = 41 + -1u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add 'u' to each side of the equation. 52 + u = 41 + -1u + u Combine like terms: -1u + u = 0 52 + u = 41 + 0 52 + u = 41 Add '-52' to each side of the equation. 52 + -52 + u = 41 + -52 Combine like terms: 52 + -52 = 0 0 + u = 41 + -52 u = 41 + -52 Combine like terms: 41 + -52 = -11 u = -11 Simplifying u = -11

| 4x-3(x-4)=-11 | | 0.3x=1 | | -46=3x+7 | | 17x-8=3x+16 | | 4x-9(x-1)=20-5x | | 13=-2+3w | | 4x+5=4x-1 | | 11x+25=7x+15 | | 8x-2(x-8)=-14 | | 7x+3=7x+3 | | 8x+11=8x+8 | | 145=10x-8x | | -30-42= | | -30+-42= | | -31=8-6p-7p | | 15+7x=45 | | 6x-4(x-6)=-10 | | 3f=17 | | -12n-19=77 | | 4n+8=12 | | 3c-4=5 | | 19=10-b | | y+8=3x | | 3a+5a=16 | | 16x-4x=36 | | 4y+7y=22 | | 12m-3m=18 | | 5p+2p=28 | | 23z-13z=50 | | 5c-4=8c+2 | | -4(3-p)=5(p+1) | | 5x+9+7x=0 | | 10-2x=19-4x | | 2(3x+6)-4(x-2)=24 | | 7x+6y= | | 7-(11-2x)=6 | | 3(x-7)-2(x+11)=21 | | 8x-4=60 | | 6x-(4x-4)=14 | | 5y-7=15y+63 | | 5x+5=3x+53 | | 4(x-2)+16=3(x+5) | | 9x=8x-6 | | 9x-8x=8x-8x-432 | | 4(3x+2)=44 | | 5x+3=13+3x | | 4x+3=6x-9 | | 6+16x=16x-12 | | 4x-16=7x+2 | | 7w-8w=-4w-30 | | 6(b-4)=6b-24 | | 9w-2=-w-22 | | 2p+11=-13 | | -15(-4)+(-37)= | | -x+5=-4+71 | | (5y+1)(8-y)=0 | | 3x-6+2x=8x+3 | | 3(x-2)+2x=4(2x+3) | | 2(5x-3)=4 | | 12=3x-15 | | -5x+9=9+6x | | 2x+7=19-4x | | -7x-1=5x-145 | | 7-2x=21 | | 3x+4=-59-6x |